A Brief Review of the Latest Intervention Methods for Sleep Disorders in Children with Autism Spectrum Disorder - Li, Junmin; Wang, Lulu (International Journal of Public Health and Medical Research, 2025)
Up to 80% of children with autism spectrum disorders (ASD) experience sleep disorders, which can manifest in five predominant forms. Although the causes of sleep disorders in these children remain unclear, the relationship between autism—considered a neurodevelopmental disorder—and the critical role of sleep in neurodevelopment has prompted significant interest among researchers and clinicians. Over the past decade, numerous trials have explored both non-pharmacological and pharmacological interventions to improve sleep in children with autism. A review of numerous randomized controlled trials on sleep in children with autism has shown that, while no definitive conclusions have been reached regarding the most effective intervention, melatonin appears to be the most promising option based on its widespread use in studies. Recent experimental evidence also addresses concerns from earlier research about the long-term efficacy and safety of melatonin. However, further exploration is needed to determine the most effective doses of melatonin for different severities of sleep disorders.